2022
DOI: 10.3389/fmed.2022.952977
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of new phytotherapy on human macrophages and TLR4- and TLR7/8-mediated viral-like inflammation in mice

Abstract: BackgroundWhile all efforts have been undertaken to propagate the vaccination and develop remedies against SARS-CoV-2, no satisfactory management of this infection is available yet. Moreover, poor availability of any preventive and treatment measures of SARS-CoV-2 in economically disadvantageous communities aggravates the course of the pandemic. Here, we studied a new immunomodulatory phytotherapy (IP), an extract of blackberry, chamomile, garlic, cloves, and elderberry as a potential low-cost solution for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…The results of the current study are in line with the conclusions of other authors who note that SVM is a robust classification algorithm that provides high accuracy by transforming data into a high-dimensional feature space, where there is a maximum margin for class separation [31,[40][41][42]. While the accuracy of ML classifiers is lower than conventional threshold-based ROC, their usefulness is better due to the generalisation function: although the expansion of the tested group can give a significantly lower result than when using threshold-based ROC, ML classifiers can maintain their accuracy and generalisation quality, which depend only on the representativeness of the training set.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current study are in line with the conclusions of other authors who note that SVM is a robust classification algorithm that provides high accuracy by transforming data into a high-dimensional feature space, where there is a maximum margin for class separation [31,[40][41][42]. While the accuracy of ML classifiers is lower than conventional threshold-based ROC, their usefulness is better due to the generalisation function: although the expansion of the tested group can give a significantly lower result than when using threshold-based ROC, ML classifiers can maintain their accuracy and generalisation quality, which depend only on the representativeness of the training set.…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies using standardized herbal cocktails reported the efficacy of chronic treatment with herbs that exerted antioxidant and anti-inflammatory effects [ 278 , 295 ]. For example, standardized herbal cocktail (SHC), an extract of clove, bell pepper, basil, pomegranate, nettle and other plants that was designed as an antioxidant treatment, was reported to reduce signs of increased depressive and aggressive behaviour in mice subjected to a model of ultrasound “emotional” stress, and in the paradigm of enhanced learning of adversities/PTSD [ 63 ].…”
Section: New Strategies In Pharmacological Management Of Pathological...mentioning
confidence: 99%
“…The deficits in the marble test and increased floating behavior in naive mutants are likely to be associated with increased baseline TNF and COX-1 expression in the PFC and HIP ( Puppala et al, 2021 ). The suppression of exploratory novel cage activity in both genotypes after LPS challenge might be explained by the short delay between the inflammatory challenge and the assay, and a ceiling pro-inflammatory effects on mouse behavior ( Schapovalova et al, 2022 ; Yates et al, 2022 ). The lack of these group differences also rules out possible confounds in measuring reported LPS-induced behavioural responses of two genotypes in other tests, which might have, potentially, been caused by distinct genotype changes in general activity after LPS injection.…”
Section: Discussionmentioning
confidence: 99%